PENDAPATAN MASYARAKAT DARI PROGRAM PENGELOLAAN HUTAN BERSAMA MASYARAKAT (PHBM) DENGAN SISTEM AGROFORESTRI (Studi Kasus : Desa Sumberejo BKPH Nglawungan KPH Blora Devisi Regional I Jawa Tengah Perum Perhutani) - Listriyani, Tria; Lidiawati, Ina; Rusli , Abdul Rahman (Jurnal Nusa Sylva, 2022)
Community based forest management is believed to be able to increase agricultural and timber products, which has economic value. Farmers generally pay more attention to economic factors than to maintaining agricultural land and forests. The level of crop productivity and the income scale of agroforestry farmers are affected by the area of agroforestry land, so it needs to be maintained. This study aims to determine the pattern of agroforestry planting and community income from the Community Forest Management (PHBM) program with an agroforestry system in Sumberejo Village BKPH Nglawungan KPH Blora Perum Perhutani Regional Division I Central Java. The method used was purposive sampling with a survey approach. The sample was selected from 6 KTH, where each is 5-7 representative respondents with criteria of the land area of ​​0.25-0.1, active members of LMDH for at least one year, and farming for at least two years as well as heads of families who were sampled in this study. The research analysis uses the Pd = TR – TC formula, and the data analysis uses descriptive analysis based on tabulations. The results showed that the community participating in PHBM in Sumberejo Village was dominated by those aged more than 30 years, with an elementary school (SD) graduate education level and livelihood as agricultural workers. Application of the pattern with an agroforestry system is with a row pattern (alternate rows). The agroforestry component is agrisilviculture, with an average farmer income of IDR 24,691,320 in a year.